High‐grade serous peritoneal cancer follows a high stromal response signature and shows worse outcome than ovarian cancer. Issue 1 (23rd October 2020) - Jacob, Francis; Marchetti, Rosa Lina; Kind, André B.; Russell, Kenneth; Schoetzau, Andreas; Heinzelmann‐Schwarz, Viola A.
Abstract : In the era of personalized medicine, where transition from organ‐based to individualized genetic diagnosis takes place, the tailoring of treatment in cancer becomes increasingly important. This is particularly true for high‐grade, advanced FIGO stage serous adenocarcinomas of the ovary (OC), fallopian tube (TC), and peritoneum (PC), which are currently all treated identically. We analyzed three independent patient cohorts using histopathologically classified diagnosis and various molecular approaches (transcriptomics, immunohistochemistry, next‐generation sequencing, fluorescent and chromogenic in situ hybridization). Using multivariate Cox regression model, we found that PC is more aggressive compared with advanced‐stage OC independent of residual disease as shown by an earlier relapse‐free survival in two large cohorts (HR: 2.63, CI: 1.59–4.37, P < 0.001, and HR: 1.66, CI: 1.04–2.63, P < 0.033). In line with these findings, transcriptomic data revealed differentially expressed gene signatures identifying PC as high stromal response tumors. The third independent cohort ( n = 4054) showed a distinction between these cancer types for markers suggested to be predictive for chemotherapy drug response. Our findings add additional evidence that ovarian and peritoneal cancers are epidemiologically and molecularly distinct diseases. Moreover, our data also suggest consideration of the tumor‐sampling site for future diagnosis and treatment decisions. Abstract : Serous peritoneal and high‐grade serous ovarian/tubal cancers are treated identically with maximal cytoreductive surgery and platinum‐based chemotherapy. Here, we provide epidemiological, clinical, and molecular evidence that peritoneal cancer is more aggressive and shows a distinct molecular signature on gene and protein levels. Our data suggest alternative treatment decisions and to consider the tumor‐sampling site for diagnosis in the future.